Effectiveness and biochemical basis of wholemeal GlutoPeak test in predicting water absorption and gluten strength of Canadian hard red spring wheat. Issue 4 (8th April 2021) - Wang, Kun; Sangha, Jatinder; Cuthbert, Richard; Fu, Bin Xiao
Abstract: Background and objectives: To further improve the efficiency of GlutoPeak test for selecting water absorption and gluten strength in wheat breeding programs, this study was conducted to investigate the suitability and effectiveness of wholemeal as testing material by eliminating flour milling process which is often the bottleneck of quality evaluation throughput. Findings: By analyzing forty‐four advanced wheat lines, strong correlations were found for wholemeal GlutoPeak parameters with conventional flour‐based farinograph absorption ( r = .82, p < .001) and stability ( r > .76, p < .001), and extensigraph Rmax ( r > .90, p < .001). The secondary structures of gluten proteins, collected at different mixing stages of GlutoPeak test, were examined using Fourier transform infrared (FTIR) spectroscopy. The β‐turn structure increased significantly from partially developed to fully developed gluten, indicating its critical role in contributing to gluten viscoelasticity. Conclusions: Without the preparation of refined flour, wholemeal GlutoPeak test can be a powerful tool for rapid and effective selection of key wheat quality traits. Significance and novelty: This study demonstrated the effectiveness of wholemeal GlutoPeak test in screening key wheat quality parameters. The changes in gluten protein secondary structure during GlutoPeak test (refined flour or wholemeal) were demonstrated for the first time.